Bridging the Gap: The Impact of Psychological Support on Academic Performance and Achievement Motivation among Orphaned and Non-Orphaned Adolescents in Uttarakhand Schools - Vinwal, Shikha; Joshi, Prof. Jyoti (Journal of Innovation in Education and Social Research, 2024)
This study investigates the impact of psychological support systems, particularly counseling services, on the academic performance and achievement motivation of orphaned and non-orphaned adolescents in Uttarakhand government schools. Using a mixed-methods approach, the research examines the availability, accessibility, and efficacy of counseling services for 122 participants (61 orphaned and 61 non-orphaned adolescents) across three schools. The study reveals a significant lack of professional counseling services, with orphaned students facing disproportionate challenges in emotional well-being and academic performance. Non-orphaned students, while experiencing fewer emotional difficulties, report higher rates of academic challenges. The research highlights disparities in access to informal support systems, with orphaned adolescents relying more on institutional figures and non-orphaned students benefiting from parental guidance. While counseling services positively impact academic performance for 84.43% of students, the benefits are more pronounced for non-orphaned students, suggesting the influence of social capital on counseling effectiveness. The study underscores the need for targeted interventions and comprehensive support systems to address the unique needs of orphaned adolescents and promote equitable educational outcomes.